Dampak Proses Keterbukaan Diri Pengguna Aplikasi Kencan Online Litmatch dalam Mencari Pasangan - Aldyanto, Ryo; Baswara Yua Kristama (LPPM Stikosa-AWS, 2024)
This research aims to explore and analyze self-disclosure in interpersonal communication among users of the online dating app LitMatch in their search for partners. The background of this study lies in the advancements of communication technology which have transformed interpersonal communication behaviors, particularly in partner-seeking through online dating apps. Online dating apps offer convenience, speed, and efficiency in the search process and interaction with potential partners, yet they also pose challenges related to self-disclosure in the process of social penetration among LitMatch users. This study employs a qualitative approach using phenomenological methods. Data collection techniques include in-depth interviews with LitMatch users, observation, and documentary studies. The findings reveal that LitMatch users go through stages of social penetration: orientation stage, stage of exploratory affective exchange, affective exchange stage, and stable exchange stage. The analysis indicates that most informants choose their partners based on compatible communication and frequency of interactions that lead to comfort and willingness to choose them as partners.